1991
DOI: 10.1111/j.1365-3148.1991.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of intravenous immunoglobulin on placental transfer of a platelet‐specific antibody: Anti‐P1A1

Abstract: The isolated perfused lobule of human placenta was used as an in-vitro model to study the effect of intravenous immunoglobulin (IVGG) on the placental transfer of a human platelet-specific antibody (anti-P1A1). Normal human IgG was shown to transfer from the maternal to the fetal circulation of the placental model after a lag period of 2-3 h. IVGG also transferred across the placenta but only after a longer lag period (3-4 h) than normal human IgG at the same concentration, which suggests that IVGG may contain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
13
0

Year Published

1992
1992
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 18 publications
3
13
0
Order By: Relevance
“…The transport of IgG and its subclasses from IVIgG using a placental perfusion model has also been reported by Morgan et al (1991) and Malek et al (1995). In contrast with our findings where IgG was detectable by 1 h, both authors noted a lag phase of 2 h before IgG appeared in the fetal circulation when using Sandoglobulin IVIgG (Sandoz, Berne, Switzerland).…”
Section: Discussionsupporting
confidence: 69%
See 3 more Smart Citations
“…The transport of IgG and its subclasses from IVIgG using a placental perfusion model has also been reported by Morgan et al (1991) and Malek et al (1995). In contrast with our findings where IgG was detectable by 1 h, both authors noted a lag phase of 2 h before IgG appeared in the fetal circulation when using Sandoglobulin IVIgG (Sandoz, Berne, Switzerland).…”
Section: Discussionsupporting
confidence: 69%
“…Presuming a likely maximum rate of transfer for total IgG (Fig 2B), the data suggest that there is competitive inhibition at the level of the syncytiotrophoblast Fcg receptor between specific anti-D IgG and the non-specific IgG present in IVIgG. Morgan et al (1991), in assessing the transfer of the platelet-specific antibody anti-Pl A1 [anti HPA1a], suggested that the IVIgG they used may contain an inhibitory factor, causing delayed transfer. It is unlikely that there is any anti-idiotypic interaction between IVIgG and anti-D since a negligible amount of complexed specific anti-D was recovered after PEG precipitation (Table III).…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In a similar experimental model, Duncan et al [23] found that the cotransfusion of gammaglobulin and anti-RhD IgG interfered with the movement of each other across the perfused placenta. Morgan et al [24] showed that when preceded by transfusion of gammaglobulin, the rate of the platelet antibody transport was significantly reduced. We have documented in our study the inhibition of transport of HIVIG by generic immunoglobulins.…”
Section: Introductionmentioning
confidence: 99%